PELATIHAN AKUNTANSI PENGELOLAAN KEUANGAN DESA: Pada Desa Baru Kecamatan Pancur Batu Kabupaten Deli Serdang - Melanthon Rumapea; Arthur Simanjuntak; Duma Megaria Elisabeth; Mitha Christina Ginting; Sahala Purba; Septony Benyamin Siahaan; Dompak Pasaribu; Rike Yolanda Panjaitan; Wesly Andri Simanjuntak; Januardi Mesakh (Universitas Methodist Indonesia, 2021)
The purpose of this training is to increase the knowledge of village heads and village officials about accounting, so that they can record village financial transactions accurately and correctly. The method of implementing community service activities is carried out in several stages, namely the preparation stage, implementation stage, evaluation stage and reporting stage. The results of interviews with the Village Head and Village Apparatus regarding village financial management include: 1. Planning Stage: in this stage the village head and village apparatus identify problems that exist in the field later, accommodate proposals given by the community through the Badan Permusyawaratan Desa (BPD) as well as community leaders. 2. Implementation Phase: Submissions for implementation activities can be accepted if they have completed the activity implementation documents. 3. Administration stage: the treasurer must compile a report, how much is the income and how much is the expenditure, then everything is detailed for what the funds are used for. 4. Reporting Stage: At the reporting stage, the village treasurer is responsible. The village treasurer has the obligation to record every end of the month in an orderly manner and account for money through an accountability report. 5. Accountability Stage: the village head is basically responsible to the people where the accountability procedure will be submitted to the Bupati/Walikota through the Camat.